Making and prioritizing managerial decisions using fuzzy logic and artificial neural networks - Ali, Ahmad (İstanbul Sabahattin Zaim Üniversitesi, 2022)
Management is one of the most critical factors for success in life in general. Management is important at the personal level in terms of managing money, time, effort, and other things, as well as at the level of companies and institutions and even at the level of countries. From this point of view, there was interest in the decision-making processes, and the machine had a role in this process, an example of that was its role in assisting bank owners in determining who deserves loans from others, as well as in the stock market in buying and selling operations and other matters. However, these decisions were limited to aspects and not others, which are the financial aspects, because of the ease of calculation for the machine and the availability of data that help in completing the work. However, in this thesis, we have worked to pay attention to administrative decisions in their broader concept and in their general areas, which are not limited to money only. We created a machine model that simulates human thinking using fuzzy logic systems and artificial neural networks, and then we compared the two models. The results we obtained were satisfactory, despite the scarcity of data available in this field, and we have indicated the reasons in the appropriate sections.

Yönetim, genel olarak hayatta başarı için en önemli faktörlerden biridir. Yönetim, para, zaman, emek ve diğer şeylerin yönetimi açısından kişisel düzeyde olduğu kadar şirketler ve kurumlar düzeyinde ve hatta ülkeler düzeyinde de önemlidir. Bu açıdan bakıldığında, karar alma süreçlerine ilgi vardı ve makinenin bu süreçte rolü vardı, bunun bir örneği banka sahiplerine kimin diğerlerinden krediyi hak ettiğini belirlemede ve bunun yanı sıra kredi verme sürecindeki rolüydü. Borsa alım satım işlemleri ve diğer konularda. Ancak, bu kararlar, makine için hesaplama kolaylığı ve işin tamamlanmasına yardımcı olan verilerin mevcudiyeti nedeniyle, finansal yönler olan diğer yönlerle değil, yönlerle sınırlıydı. Ancak bu tezde, idari kararların sadece para ile sınırlı olmayan, daha geniş kavramı ve genel alanları ile dikkate alınmasına çalıştık. Bulanık mantık sistemleri ve yapay sinir ağları kullanarak insan düşüncesini simüle eden bir makine modeli oluşturduk ve ardından iki modeli karşılaştırdık. Elde ettiğimiz sonuçlar bu alandaki verilerin azlığına rağmen tatmin ediciydi ve nedenlerini uygun bölümlerde belirttik.
Bulanık mantık ve yapay sinir ağları kullanarak yönetsel kararların verilmesi ve önceliklendirilmesi
Keywords: Managerial decisions; Fuzzy logic; Deep learning; Artificial neural network; Machine learning; Priorities in decisions; Yönetsel kararlar; Bulanık mantık; Derin öğrenme; Yapay sinir ağı; Makine öğrenmesi; Kararlarda öncelikler